Interest and motivation in learning with application for college education - Olmstead, Cassandra (My University, 2018)
This study examined the role that interest plays in the motivation to learn. The study consisted of three phases. In the first phase participants completed an online survey to determine their interest in either sports or superheroes. Next participants were randomly assigned to view either a PowerPoint presentation with a sports theme or a heroes theme. Based on the match or mismatch of their indicated interest and the PowerPoint they viewed, participants were considered to be in the congruent group, incongruent group, or neutral group (those who rated a theme neither high or low). Results showed that interest increased motivation to study. The neutral group scored higher than the incongruent group on application questions, indicating deeper understanding of the material. However, these unexpected results indicated that further research into the possible role of seductive details, and interest as a whole, in motivation and retention is needed.
Keywords: Motivation in education; Learning; Interest; Learning; Motivation; Seductive details; Student success; Study time